Unravelling the interphase - bond strength relationship in novel co-bonded thermoplastic - thermoset hybrid composites for leading edge protection of wind turbine blades - Ozan Erartsin; Jamal Sayyed Monfared Zanjani; Ismet Baran (Polymer Testing, 2023)
The relation between the bond strength of the co-bonded thermoplastics (ABS, PC) and fiber-reinforced thermoset polymers (polyester/glass) and the interphase morphology of a novel integrated leading edge protection (LEP) solution for wind turbine blades is investigated. Interphase morphology is characterized via optical microscopy and the mechanical properties of the interphase are obtained by means of nanoindentation. Bond strength of the co-bonded hybrid composites is tested via climbing drum peel test, after which, fractography is carried out to link the fracture behavior to interphase morphology. It was seen that ABS establishes a stronger bond with polyester/glass, constituting a better candidate as an LEP material. The superior bond strength of ABS was linked to its higher affinity to polyester, promoting a no-phase separated, tough interphase undergoing extensive plastic deformation. The interphase between PC and polyester/glass, however, exhibited phase separation, which triggered brittle failure at the interface between the interphase and the polyester/glass.